Die Lemmatisierung von Goethes "Wahlverwandtschaften" - Martina Schwanke (Hermes, 1993)
In German studies computer-oriented methods are taking on an increasing significance and consequently should be considered in detail together with all the problems connected with them. This article deals with the automatic lemmatization of Goethe's novel "The Elective Affinities". Following the results of the computer-system LEMMA2, central problems of lemmatization as far as manual correction is concerned will also be discussed.